Ladybird beetles - recent immigrants to Florida (Insecta: Coleoptera: Coccinellidae) - Michael C. Thomas; Orland J. Blanchard, Jr (EDIS)
Since the publication of the Florida beetles checklist, a few ladybird beetles have become established in the state, some well-known and extensively documented and some little noticed and previously unreported. It is these latter species that are covered in this publication. All of the listed species are represented by voucher specimens in the Florida State Collection of Arthropods. Species previously known from Florida are reported by Frank and Mizell (2012) with emphasis on natural history. This 5-page fact sheet was written by Michael C. Thomas and Orland J. Blanchard, Jr., and published by the UF Department of Entomology and Nematology, October 2013.